Changing times: does the critical success factors boosting green transition of SMEs remain unchanged? - Pham Quang Huy; Vu Kien Phuc (Journal of Innovation and Entrepreneurship)
Abstract This study aims to conduct a thorough analysis to determine the key elements that contribute to the behavioral intention of small and medium enterprises (SMEs) to adopt green transition. The statistical data used in this study were obtained from two rounds of data collected from individuals working in SMEs. This work utilized structural equation modeling to analyze the hypothesized interlinks. The analysis of the results confirmed the positive relationships between key elements in terms of their significance and effect size. The most stable elements of intention of green transition implementation were determined based on the degree of stability of the findings. In addition to expanding our understanding of the advantages of green transition in SMEs, the results of this study can provide guidance to SME leaders on how to improve their efficiency and effectiveness in the process of green transition practices. A more detailed understanding in this research can provide policymakers with the ability to establish laws and regulations for the transition towards sustainability.